Droplet digital polymerase chain reaction assay and peptide nucleic acid‐locked nucleic acid clamp method for RHOA mutation detection in angioimmunoblastic T‐cell lymphoma. Issue 5 (31st March 2018) - Tanzima Nuhat, Sharna; Sakata‐Yanagimoto, Mamiko; Komori, Daisuke; Hattori, Keiichiro; Suehara, Yasuhito; Fukumoto, Kota; Fujisawa, Manabu; Kusakabe, Manabu; Matsue, Kosei; Wakamatsu, Hirotake; Shimadzu, Mitsunobu; Chiba, Shigeru
Abstract : Angioimmunoblastic T‐cell lymphoma (AITL) is a subtype of nodal peripheral T‐cell lymphoma (PTCL). Somatic RHOA mutations, most frequently found at the hotspot site c.50G > T, p.Gly17Val (G17V RHOA mutation) are a genetic hallmark of AITL. Detection of the G17V RHOA mutations assists prompt and appropriate diagnosis of AITL. However, an optimal detection method for the G17V RHOA mutation remains to be elucidated. We compared the sensitivity and concordance of next‐generation sequencing (NGS), droplet digital PCR (ddPCR) and peptide nucleic acid‐locked nucleic acid (PNA‐LNA) clamp method for detecting the G17V RHOA mutation. G17V RHOA mutations were identified in 27 of 67 (40.3%) PTCL samples using NGS. ddPCR and PNA‐LNA clamp method both detected G17V mutations in 4 samples in addition to those detected with NGS (31 of 67, 46.3%). Additionally, variant allele frequencies with ddPCR and those with NGS showed high concordance ( P < .001). Three other RHOA mutations involving the p.Gly17 position (c.[49G > T;50G > T], p.Gly17Leu in PTCL198; c.[50G > T;51A > C], p.Gly17Val in PTCL216; and c.50G > A, p.Gly17Glu in PTCL223) were detected using NGS. These sequence changes could not appropriately be detected using the ddPCR assay and the PNA‐LNA clamp method although both indicated that the samples might have mutations. In total, 34 out of 67 PTCL samples (50.7%) had RHOA mutations at the p.Gly17 position. In conclusion, our results suggested that a combination of ddPCR/PNA‐LNA clamp methods and NGS are best method to assist the diagnosis of AITL by detecting RHOA mutations at the p.Gly17 position. Abstract : Angioimmunoblastic T‐cell lymphoma (AITL) is a distinct subtype of nodal peripheral T‐cell lymphoma (PTCL). Somatic RHOA mutations, (most frequently c.G50T, p.G17V RHOA mutation) are a genetic hallmark of AITL. Our results showed that a combination of NGS, ddPCR and PNA‐LNA clamp methods increased the detection rate of RHOA mutations at the p.G17 position.